2021
DOI: 10.30630/joiv.5.2.373
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things-Based Energy Efficiency Optimization Model in Fog Smart Cities

Abstract: In recent years, the IoT) Internet of Things (IoT) allows devices to connect to the Internet that has become a promising research area mainly due to the constant emerging of the dynamic improvement of technologies and their associated challenges. In an approach to solve these challenges, fog computing came to play since it closely manages IoT connectivity. Fog-Enabled Smart Cities (IoT-ESC) portrays equitable energy consumption of a 7% reduction from 18.2% renewable energy contribution, which extends resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A wide range of socioeconomic challenges can now be addressed through the processing of sensory input at the network's edge. Edge-based computing offers many benefits for industries such as Industry 4.0 [18], [19], building automation [20], smart cities [17], and healthcare [21], in part because it reacts quickly to fast-moving events [22,23] and delivers operational benefits. Research in IoT has mainly focused on edge-based IoT data management to meet data-driven applications-specific demands.…”
Section: Applications Of Iot Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of socioeconomic challenges can now be addressed through the processing of sensory input at the network's edge. Edge-based computing offers many benefits for industries such as Industry 4.0 [18], [19], building automation [20], smart cities [17], and healthcare [21], in part because it reacts quickly to fast-moving events [22,23] and delivers operational benefits. Research in IoT has mainly focused on edge-based IoT data management to meet data-driven applications-specific demands.…”
Section: Applications Of Iot Heterogeneitymentioning
confidence: 99%
“…In this study, it is demonstrated that the IoT has increased energy consumption, and the summary study illustrates the latest proposed methods in energy management across different belts such as smart homes, smart buildings, and smart grids. In addition, Jiang et al [17] conducted a study on IoTbased smart city information system building and cloud computing. This study illustrates that this system can share information sharing, exchange, and fusion between different sensing subsystems, thereby solving the problem of previous information islands and serving the real needs of smart cities.…”
Section: A Fusion Iot Network For Forwarder Selectionmentioning
confidence: 99%
“…The QL embraces diverse alternatives entailing the deep QL, Double QL, and Delayed QL. Based on [36]. The Greedy (GQL) rummage sale in the practice in amalgamation with occupation approximation and conjunction [37].…”
Section: Q-learningmentioning
confidence: 99%
“…5G operators will have full visibility, and inspection. To implement such a rigorous security system, 5 G providers would have complete visibility, monitoring, and control of total network layers [65].…”
Section: Visibilitymentioning
confidence: 99%